2019
DOI: 10.1155/2019/7630926
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Apple Lesions in Orchards Based on Deep Learning Methods of CycleGAN and YOLOV3-Dense

Abstract: Plant disease is one of the primary causes of crop yield reduction. With the development of computer vision and deep learning technology, autonomous detection of plant surface lesion images collected by optical sensors has become an important research direction for timely crop disease diagnosis. In this paper, an anthracnose lesion detection method based on deep learning is proposed. Firstly, for the problem of insufficient image data caused by the random occurrence of apple diseases, in addition to traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 27 publications
1
82
0
1
Order By: Relevance
“…The CycleGAN [102] is essentially two mirror-symmetrical GAN, it can learn the characteristics of a class of data and generate similar data. The research showed that compared with traditional image enhancement methods, the CycleGAN method greatly enriched the diversity of training data sets [103].…”
Section: Analysis Of the Surveyed DL Applicationsmentioning
confidence: 99%
“…The CycleGAN [102] is essentially two mirror-symmetrical GAN, it can learn the characteristics of a class of data and generate similar data. The research showed that compared with traditional image enhancement methods, the CycleGAN method greatly enriched the diversity of training data sets [103].…”
Section: Analysis Of the Surveyed DL Applicationsmentioning
confidence: 99%
“…Machine learning, for an instance, plays a key role in detecting such pests and epidemics. In the past decades, a considerable volume of studies with different machine learning algorithm have been executed for Plant disease detection under different environmental conditions, in different countries, and for different plants such as tomato [7], potato [8], rice [9], cassava [10], mango [11], apple [12,13] , general plants [14,15], and Olive [16,17], etc. Jagan Mohan et al [4] presented a system that firstly used SIFT to extract featured from the paddy plant; secondly the AdaBoost classifier was used for disease detection with identification rate 83.33%.…”
Section: Related Workmentioning
confidence: 99%
“…Singh, et al [11] presented a multilayer convolutional neural network (MCNN) based approach for identifying Anthracnose fungal disease affect Mango leaves, the system get average accuracy of 97.13%. Detection of anthracnose lesion in apple fruit using adapted DenseNet model was presented in [12], and it achieved an overall accuracy of 95.57% for disease identification. Apple leaf diseases using deep-CNNs is proposed in [13], in this system; GoogLeNet Inception structure and Rainbow concatenation (VGG-INCEP model.)…”
Section: Related Workmentioning
confidence: 99%
“…The problem of fruit detection is also widely analyzed in the literature, especially during the detection of fruits in orchards [19] and damage detection [20]. The YOLO V3 model [18], the Faster R-CNN model [21], and their modifications are the state-of-the-art fruit detection approaches [19,20]. The use of object detection and recognition techniques for multi-class fruit classification was presented in [22].…”
Section: Related Workmentioning
confidence: 99%